CRIMES IN THE SPHERE OF TELECOMMUNICATIONS AND COMPUTER INFORMATION AS A THREAT TO THE NATIONAL SECURITY OF THE COUNTRY - D. K. Chirkov; A. Z. Sarkisyan (Russian Journal of Economics and Law)
Objective: to research the criminality in the sphere of telecommunications and computer information and elaborate efficient measures of its prevention. Methods: ascent from the abstract to the specific; systemic-structural analysis; historical method; dynamic and statistical methods, specific-sociological methodology of estimating criminality. Results: the features of crimes in the sphere of telecommunications and computer information are shown by their public threat. Efficient preventive measures are suggested. Scientific novelty: analysis is carried out of dynamics of crimes in the sphere of telecommunications and computer information registered in the Russian Federation, to the number of Internet users in 2009–2012. Conclusions are made that the viewed crimes are latent. Practical value: The research results allow to trace the level of latency of such crimes, and to optimize measures for their counteraction.